The complication : a program novel - Young, Suzanne (The Program series, 2018)
Seventeen-year-old Tatum Masterson has no memory of being in The Program, but when she starts experiencing crashbacks she knows something terrible happened last summer, and with help from the boyfriend she lost, Tatum digs into the past and future of The Program and its handlers, and discovers the true cost of a cure.